Esthetic preferences of laypersons of different cultures and races with regard to smile attractiveness - Amir Houman Sadrhaghighi; Afsaneh Zarghami; Shahrzad Sadrhaghighi; Amir Mohammadi; Mahsa Eskandarinezhad (Wolters Kluwer Medknow Publications, 2017)
Background: Culture and ethnicity are among the factors affecting esthetic judgment of individuals. Aims: This study aimed to assess the acceptability threshold of variations in four components of an esthetic smile namely vertical lip thickness, dental midline deviation, buccal corridor, and the golden ratio in maxillary lateral incisors display among laypersons of different races and cultures. Subjects and Methods: Raters (n = 35 in each city) among laypersons of nine cities namely Istanbul, Isfahan, Tabriz, Tehran, Doha, Rome, Sydney, Chicago, and Yazd, were given a photo album containing 27 random images of an attractive female smile, digitally altered with regard to the four smile components. They scored each picture from 0 to 100 in terms of smile attractiveness. Statistical Analysis: Data were analyzed using SPSS 13 and the acceptability threshold for each component was calculated in each city using the Spearman and Wilcoxon tests. P< 0.05 was considered statistically significant. Results: No significant differences were noted with regard to the increased vertical lip thickness, and an acceptability threshold could not be determined for it. The acceptability thresholds for midline deviations, buccal corridor, and the golden ratio were different among different cities. One-millimeter increase in the displayed width of maxillary lateral incisors was more desirable than the golden ratio standard width. Conclusion: Culture and race may significantly affect the esthetic preference of individuals with regard to smile attractiveness.